The Challenges of Raising Revenues and Restructuring Subsidies in Malaysia - Suresh Narayanan , (Kajian Malaysia, 2007)
Malaysia has run deficit budgets in all but five years since 1970 but past deficits have been managed thanks to substantial oil revenues and high domestic savings. However, the slow growth or decline of several traditional sources of revenue and the rising subsidy bill since 2007 have given pause for reflection on the traditional approach to fiscal management. In this paper, it is argued that fiscal management must not only centre around reducing non-productive expenditures and wasteful leakages but must also confront the problem of reducing and restructuring subsidies, particularly to petrol and petroleum-related products. The global dip in petroleum process has fortuitously provided the respite needed for such an exercise and should not lull policy makers into complacency. When the economy recovers from the current downswing, a solid revenue raising instrument such as the value-added tax must be introduced in order to wean the economy away from the current over reliance on petroleum-based taxes.